Assessing the Efficacy and Fairness of Traditional and Open Peer Review in Academic Publishing - Samoaa, Peter (My University, 2024)
This report investigates the prevailing attitudes toward traditional and open peer review systems among researchers in computer science. Through an analytical survey conducted with a diverse group of participants, including faculty members and students with varying publication records, we explore the perceived efficacy, fairness, and quality of both review processes. Particular attention is given to the consistency of respondents' answers, examining the correlation between their general opinions on peer review and their specific experiences with comment quality. The study aims to assess whether open peer review can address the shortcomings of the traditional system, taking into account the role of respondent and their experience in research.